Analisa Pengaruh Produktifitas Terhadap Biaya Operasional Pada Proyek Penggalian Ex Disposal NW01B Guna Pengambilan Batubara di PT. Pamapersada Nusantara Distrik KMIA - Parulian, Boy; Syarip, Firman (Universitas Pendidikan Ganesha, 2022)
PT Pamapersada Nusantara is one of the companies in Indonesia that is engaged in coal mining contractors. One of the main activity by the company is the overburden removal and coal mining in accordance with the production targets agreed with the customer. Based on the annual production planning 2022, to achieve the customer's production target, there is one work area in the KAKAO Pit – R5B west side which is the disposal of NW01B above the mineout Pit NW01B. The Disposal will be cutback (removing the overburden) for the purpose of coal mineout. Based on survey data, the total volume of disposal cutback is 3.9 Mbcm. Technical analysis states that there is a decrease in productivity by 10%, a decrease in productivity affects a decrease in production capacity which has implications for an increase in operational costs about IDR 7.12 M. To accommodate the increase in operational costs, to maintain the company's profitability, an analysis of the proposed price adjustment of the overburden excavation about USD 0.1259/bcm.